The December 2017 Hojedk (Iran) earthquake triplet—sequential rupture of shallow reverse faults in a strike-slip restraining bend. Issue 2 (31st January 2019) - Savidge, Elena; Nissen, Edwin; Nemati, Majid; Karasözen, Ezgi; Hollingsworth, James; Talebian, Morteza; Bergman, Eric; Ghods, Abdolreza; Ghorashi, Manouchehr; Kosari, Ehsan; Rashidi, Ahmad; Rashidi, Ali
SUMMARY: A triplet of M w ∼6 earthquakes on 2017 December 1–12 occurred ∼50 km north of Kerman, Iran, in an area of mountainous topography where several major right-lateral strike-slip fault systems—the Gowk, Nayband, Lakar Kuh and Kuh Banan faults—converge. Here we assess their source parameters and surficial expression using regional and teleseismic waveforms and arrival times, synthetic aperture radar interferometry, optical satellite image correlation and field observations. All three main shocks occurred on shallow reverse faults associated with the southern termination of the Lakar Kuh right-lateral strike-slip fault. The first two main shocks on 1 December and 12 December (08:43 UTC) likely ruptured and reruptured a previously unrecognized, blind, NE-dipping fault beneath the Mian Kuh range. Slip in both earthquakes extends much further along strike than down dip, hinting at structural or stratigraphic controls on rupture dimensions. The third main shock on 12 December (21:41 UTC) is perhaps the most interesting of the three events. It ruptured a conjugate SW-dipping thrust in the hangingwall of the first fault, generating a sinuous fault scarp in the alluvial plain north of the Mian Kuh range, consistent with its unusually shallow centroid depth of ∼2 km. Its high ratio of net surface slip (average ∼1.5 m and maximum ∼2.5 m) to length (∼7 km) and its narrow down-dip width (∼6 km) implies a very high stress drop. The surface rupture aligns along-strike with larger scarps that contain uplifted and incised fan surfaces in their hangingwalls, but this subtle expression of active faulting had not been fully recognized prior to these earthquakes. The clustering in space and time of large, shallow earthquakes on hidden faults is of broad concern for seismic hazard assessment in mountainous parts of Iran and in other collisional settings.